Respuesta :

Answer:

(x² - 8x + 16) = (x-4) (x-4)

Step-by-step explanation:

We have to factorize the given expression

(x²-8x+16)

(x² - 8x + 16 ) = x² - 2(4x) + 4²

                    = ( x-4)²

[As we know (a-b)² = a² + b² - 2ab]

so (x² - 8x + 16) = (x-4) (x-4) is the factored form of the given expression.

Here we need to see which factored expression is equivalent to the polynomial x^2 - 8x + 16.

We will find that the correct option is: (x - 4)^2

Now let's see how to get this.

Remember the expansion:

(x + a)^2 = x^2 + 2*a*x + a^2

In our polynomial x^2 - 8x + 16 we can see that the second term is negative, thus we must have something like:

(x - a)^2 = x^2 - 2*a*x + a^2

Also the constant digit is 16, then:

a^2 = 16

a = √16 = 4

Thus the polynomial is: (x - 4)^2

Expanding this we get:

(x - 4)^2 = x^2 - 2*4*x + 16 = x^2 - 8*x + 16

If you want to learn more, you can read:

https://brainly.com/question/12787576